"Short report" staffing in practice: five years' experience of a consultant based service in obstetrics and neonatal paediatrics. Issue 6728 (31st March 1990) - Hare, M J; Miles, R N; Lattimore, C R; Southern, J P
Abstract : Recent government plans include the concept of a core of doctors of intermediate grade providing 24 hour emergency cover in hospital departments. Hinchingbrooke Hospital has, since its opening in 1983, been run on a two tier basis, with consultants and a part time senior registrar supported only by senior house officers in their first post, usually on general practice vocational training schemes. With a planned rate of around 2000 deliveries per year all high risk obstetric and neonatal paediatric procedures, including ventilation of very small babies, have been carried out within the hospital. A study of the first five complete years of operation of the obstetric and paediatric departments showed that the perinatal mortality rate was low (hospital rate 4.7/1000 in 9149 deliveries during 1984-8 v district rate 5.1/1000 during 1986-8), and patient satisfaction seemed to be high. In a separate prospective study of out of hours work performed by consultants in paediatrics (four weeks) and obstetrics (20 days) three consultants in paediatrics spent 71 hours working out of hours; for the obstetricians, of the 56 request for advice and 38 interventions, only five and six respectively occurred between midnight and 9 am. Although successful at this hospital, the two tier system would be expensive under the Royal College of Obstetricians' guidelines of one consultant to a maximum of 500 deliveries. An equal mixture of two tier and three tier systems might be the best solution for patient care and training of junior doctors.